CRIMINAL SANCTIONS OF IMPOVERISHMENT AGAINST CORRUPTORS IN THE ERADICATION OF CORRUPTION CRIMES IN INDONESIA - Mukhammad Ardiansyah Tri Saputra; Abdul Rokhim; Nofi Sri Utami (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This research is motivated by the fact that criminal sanctions given to perpetrators of corruption do not provide any deterrent effect at all, instead causing the number of corruption cases in Indonesia to increase. So it is necessary to make a new breakthrough in criminal sanctions against corruptors, namely in the form of impoverishment. The formulation of the problem in this research is how are the regulations and concepts of criminal sanctions for impoverishment against corruptors in eradicating criminal acts of corruption in Indonesia? The research method used is normative juridical with a conceptual approach method and a legislative approach. The prevailing laws and regulations, especially the Corruption Law, do not yet contain explicit provisions that regulate impoverishment as a form of criminal punishment. Therefore, legal reform is needed by adding articles on impoverishment in the Corruption Law by grouping them based on the amount of state losses and the proportional distribution of assets. This is done because the Criminal Asset Confiscation Bill does not specifically regulate corruption, but rather several criminal acts. Impoverishment of corruptors is not enough just by confiscating assets from the proceeds of crime, but also needs to include complete confiscation of assets and restrictions on the rights and social dignity of perpetrators of corruption. The impoverishment mechanism for corruptors can be seen in the Criminal Asset Confiscation Bill, namely by confiscating assets without waiting for a criminal verdict, which allows the state to confiscate and take back assets from the proceeds of crime in certain situations such as the perpetrator being a fugitive, deceased, unknown, or unable to be prosecuted.